Mutation intolerant genes and targets of FMRP are enriched for nonsynonymous alleles in schizophrenia. Issue 7 (18th July 2017) - Leonenko, Ganna; Richards, Alexander L.; Walters, James T.; Pocklington, Andrew; Chambert, Kimberly; Al Eissa, Mariam M.; Sharp, Sally I.; O'Brien, Niamh L.; Curtis, David; Bass, Nicholas J.; McQuillin, Andrew; Hultman, Christina; et al.
Abstract : Risk of schizophrenia is conferred by alleles occurring across the full spectrum of frequencies from common SNPs of weak effect through to ultra rare alleles, some of which may be moderately to highly penetrant. Previous studies have suggested that some of the risk of schizophrenia is attributable to uncommon alleles represented on Illumina exome arrays. Here, we present the largest study of exomic variation in schizophrenia to date, using samples from the United Kingdom and Sweden (10, 011 schizophrenia cases and 13, 791 controls). Single variants, genes, and gene sets were analyzed for association with schizophrenia. No single variant or gene reached genome‐wide significance. Among candidate gene sets, we found significant enrichment for rare alleles (minor allele frequency [MAF] < 0.001) in genes intolerant of loss‐of‐function (LoF) variation and in genes whose messenger RNAs bind to fragile X mental retardation protein (FMRP). We further delineate the genetic architecture of schizophrenia by excluding a role for uncommon exomic variants (0.01 ≤ MAF ≥ 0.001) that confer a relatively large effect (odds ratio [OR] > 4). We also show risk alleles within this frequency range exist, but confer smaller effects and should be identified by larger studies.